Hippocampal non-NMDA and GABA-A receptors in benzylpenicillin-induced epilepsy and electro-acupuncture antiepilepsy - Liu Jun; Cheng Jie-Shi (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of 6,7-dinitroquinoxaline-2,3-dione (DNQX) and bicuculline (Bic) on benzyl-penicillin-induced-epilepsy (PIE) and electroacupuncture (EA) antiepilepsy in rats. METHODS: Epilepsy was elicited by intra-hippocampal microinjection of benzylpenicillin in rats. The analysis of electroencephalogram (EEG) and power spectrum was used to measure the extent of convulsion. RESULTS: EA or DNQX (1 microgram) showed partial inhibitory effect on PIE. EA + DNQX caused further inhibition of PIE, and Bic attenuated EA antiepileptic effect. CONCLUSION: Antagonization of GABA-A receptor attenuated EA antiepileptic effect, and EA acted synergistically with the antagonists of non-N-methyl-D-aspartate (non-NMDA) receptors.